The Tale of Samuel Whiskers; Or, The Roly-Poly Pudding - Potter, Beatrix, 1866-1943 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Tale of Samuel Whiskers; Or, The Roly-Poly Pudding" by Beatrix Potter is a charming children's book written in the early 20th century. This delightful tale features a mix of adventure and mischief, centering around a family of cats and their encounters with some cunning rats. The story highlights themes of escapades and the trials of being an anxious parent in a whimsical animal world. The narrative unfolds with Mrs. Tabitha Twitchit, a worried mother, searching for her mischievous son, Tom Kitten, who has decided to hide in the chimney on baking day. Meanwhile, rats Samuel Whiskers and Anna Maria plot to turn Tom into a delicious roly-poly pudding after capturing him. The story takes a turn of suspense and humor as the cats team up to rescue Tom, leading to a chaotic series of events with the rats. Ultimately, the cats outsmart the rats, leading to a satisfying resolution where the family recovers and thrives, while the rats must relocate, highlighting the blend of cleverness and humor characteristic of Potter's work. (This is an automatically generated summary.)
Release date is 2005-04-06
E-text prepared by Robert Cicconetti, Ronald Holder, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Children's stories, English; Cats -- Juvenile fiction; Rats -- Juvenile fiction